EXAMINATION OF GONAD MATURITY AND FECUNDITY ASPECT OF TOMAN FISH (Channa micropeltus) DURING RAIN SEASON PERIOD IN RAWA DANAU PANGGANG WATERS, HULU SUNGAI UTARA DISTRICT, SOUTH KALIMANTAN - Ansyari, Pahmi; Slamat, Slamat (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2018)
This study aims to find the level of gonad maturity and fecundity of toman fish living in the habitat of swamp waters Panggang Lake, Hulu Sungai Utara Regency, South Kalimantan during the rainy season period. Fish sampling were carried out every month for 3 months from January - March 2018. The method of determining the sampling location is used an analytical survey method (Analytic Survey Research Method). The results showed the gonad weight range of 11.77 to 0.18 grams and the level of gonad maturity varied from GML (gonad maturity level) I-IV, but dominated by GML I. The opportunity for fish populations to have mature gonads based on total length is 63.6% and gonad maturity index (GMI) between 0.05 - 0.73%. Fecundity results obtained 29.67% and egg diameter of 1.57 - 2.05 mm. This data shows that toman fish can spawn during the rainy season, but most of the population was maternity recovery state.